The Relationship between Anxiety and Self-Efficacy Mediated by Cognitive Flexibility in Female Students - Mirzaei Darvish Baghal, Melika; Khedmatgozar, Hossein (Health Nexus, 2025)
The present study aimed to investigate the relationship between anxiety and self-efficacy with the mediating role of cognitive flexibility among female university students. This research was a fundamental and descriptive study using a path analysis method within a correlational design. The statistical population included all female students at the Islamic Azad University, Garmsar Branch, in 2024. Using purposive and convenience sampling, 295 valid questionnaires were collected. Data were gathered using the Sherer General Self-Efficacy Scale, the Beck Anxiety Inventory, and the Cognitive Flexibility Inventory by Dennis and Vander Wal. To analyze the data, Pearson correlation coefficients and multiple regression analyses within a structural equation modeling framework were conducted using SPSS version 25 and AMOS, with a significance level set at p < .05. Pearson correlation results showed that anxiety had a significant negative correlation with both self-efficacy (r = -0.52, p < .001) and cognitive flexibility (r = -0.46, p < .001), while cognitive flexibility had a significant positive correlation with self-efficacy (r = 0.59, p < .001). The structural model revealed that anxiety significantly and negatively predicted self-efficacy (β = -0.38, p < .001) and cognitive flexibility (β = -0.36, p < .001), whereas cognitive flexibility significantly and positively predicted self-efficacy (β = 0.47, p < .001). The indirect effect of anxiety on self-efficacy through cognitive flexibility was also significant (β = -0.17, p < .001), confirming the mediating role of cognitive flexibility. Model fit indices indicated a good fit (χ²/df = 1.96, GFI = 0.93, CFI = 0.96, RMSEA = 0.047). The findings highlight the critical role of cognitive flexibility in mitigating the negative impact of anxiety on self-efficacy. Enhancing cognitive flexibility in academic and clinical settings may serve as a valuable strategy to improve self-efficacy and reduce anxiety among female students.